2005
DOI: 10.1007/s00125-005-1815-2
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of model-derived parameters of beta cell secretion during intravenous and oral glucose tolerance tests: a study of twins

Abstract: Aims/hypothesis: The genetic architecture of model-derived parameters of beta cell function has never been assessed. Therefore, we estimated heritability (h 2 ) for model-derived phenotypes of insulin secretion in twins. Methods: Thirty-three monozygotic (MZ) and 23 dizygotic (DZ) twin pairs from the Finnish Twin Cohort Study underwent an OGTT (plasma glucose/C-peptide at 0, 30, 60, 90 and 120 min). A subset of the twin pairs (21 MZ/20 DZ) also underwent an IVGTT (frequent sampling of plasma glucose/insulin fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
4
8
0
1
Order By: Relevance
“…The heritability of first-and second-phase insulin secretion in response to glucose was 52% and 77% respectively. For the first phase our results fit neatly in the 35% to 76% range of heritability estimates previously reported using the IVGTT test [6,11,[15][16][17]. However, previous heritability estimates (28% and 58%) of second-phase insulin secretion in response to IVGTT were considerably lower [11,17] than those found in our hyperglycaemic clamp.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The heritability of first-and second-phase insulin secretion in response to glucose was 52% and 77% respectively. For the first phase our results fit neatly in the 35% to 76% range of heritability estimates previously reported using the IVGTT test [6,11,[15][16][17]. However, previous heritability estimates (28% and 58%) of second-phase insulin secretion in response to IVGTT were considerably lower [11,17] than those found in our hyperglycaemic clamp.…”
Section: Discussionsupporting
confidence: 88%
“…For the first phase our results fit neatly in the 35% to 76% range of heritability estimates previously reported using the IVGTT test [6,11,[15][16][17]. However, previous heritability estimates (28% and 58%) of second-phase insulin secretion in response to IVGTT were considerably lower [11,17] than those found in our hyperglycaemic clamp. This may reflect the greater precision inherent in the clamp method in comparison to the IVGTT, but may also be due to the different stimulation of the beta cell during the second phase of both tests (maintaining 10 mmol/l glucose vs decreasing glucose level).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several lines of evidence, including twin studies (67), support the notion that the phenotype of β-cell functional mass is determined by genetic factors to quite a large extent. Over the last 6 years, genetic variability at >60 genetic loci has been firmly linked to type 2 diabetes risk (68).…”
Section: Is β-Cell Loss Of Function the Main Determinant Of β-Cell Dementioning
confidence: 94%
“…They have demonstrated significant heritable influence on glucose and insulin values, and on insulin resistance and beta cell function calculated from fasting levels or OGTT values [5][6][7][8][9][10][11][12][13][14][15], but there is no clear consensus on the degree to which genes explain the variance of fasting and 2 h glucose and insulin levels. Most studies have focused on the OGTT and have reported heritabilities of fasting and 2 h glucose and insulin ranging from 12% to 62% (see Electronic Supplementary Material [ESM] Table 1).…”
Section: Introductionmentioning
confidence: 99%